Pemenuhan nafkah terhadap anak oleh single parent perspektif sosiologi hukum Islam: Studi pada masyarakat Bangkinang Kota - Ramadhanisa, Meiyu Syahri; Arisman, Arisman; Darwis, Muhammad (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study examines the fulfillment of child maintenance obligations (nafkah) by single parents in Bangkinang Kota, Riau, Indonesia, through an Islamic legal sociology perspective. Using qualitative descriptive methodology, this research involved in-depth interviews with six single parent informants, all widowed mothers, selected through purposive sampling across four administrative areas. The study reveals that despite structural and economic challenges, single parents successfully fulfill the three main components of Islamic nafkah (food, clothing, and shelter) by implementing the principle of capability adjustment (min wus’atih) prescribed in Islamic law. They develop adaptive strategies including income diversification, social network optimization, and priority-based resource allocation that prioritize children’s needs. The findings demonstrate that single parents maintain both material and spiritual nafkah through intensive communication and moral guidance, compensating for the absence of a spouse. This research contributes to contemporary Islamic family law discourse by showing how traditional principles can adapt to modern social realities while preserving core Islamic values.